Role of HbA1c and duration of diabetes in predicting mortality in patients of diabetic ketoacidosis in type II diabetes mellitus - Sonwani, Srishti; Sonwani, Sutakshee (International Journal of Research in Medical Sciences, 2019)
Background: Previous studies have reported the presence of diabetes ketoacidosis in patients of type 2 diabetes mellitus (T2DM). India reported that up to 30% of hospitalized DKA cases result in inpatient death. Aims and objectives of the study was to study the role of HbA1c and duration of diabetes in outcome of patients of diabetic ketoacidosis in type 2 diabetes mellitus. Methods: Hundred T2DM patients having DKA admitted in the Department of Medicine, Gandhi Medical College and Hamidia Hospital, Bhopal, were included. Data on demography (age, sex and diabetes duration, random blood sugar (RBS) and glycated hemoglobin (HbA1c) were recorded for each patients. Outcome was also recorded and compared with duration of diabetes and HbA1c level. Results: DKA was more common in age group of51-55 years (21%) with mean age of 56.10±10.40 years. Male preponderance was observed. Mean duration of diabetes, hemoglobin, random blood sugar (RBS) and HbA1c were 7.28±3.81 years, 9.8±1.42 gm%, 351.72±22.32 mg/dl, and 7.14±0.10 respectively. Mortality was higher among the patients with longer duration of diabetes (23.1%; p=0.012) and higher HbA1c (25%, p>0.05). Conclusions: Duration of diabetes play a significant role in deciding mortality in T2DM patients with DKA however HbA1c has no role in that.